Chloroquine resistance evolution in Plasmodium falciparum is mediated by the putative amino acid transporter AAT1 - Alfred Amambua‐Ngwa; Katrina A. Button-Simons; Xue Li; Sudhir Kumar; Katelyn M. Vendrely; Marco Ferrari; Lisa A. Checkley; Meseret T. Haile; Douglas A. Shoue; Marina McDew‐White; Sarah M. Tindall; Ann Reyes; et al. (2023)
Abstract Malaria parasites break down host haemoglobin into peptides and amino acids in the digestive vacuole for export to the parasite cytoplasm for growth: interrupting this process is central to the mode of action of several antimalarial drugs. Mutations in the chloroquine (CQ) resistance transporter, pfcrt , located in the digestive vacuole membrane, confer CQ resistance in Plasmodium falciparum , and typically also affect parasite fitness. However, the role of other parasite loci in the evolution of CQ resistance is unclear. Here we use a combination of population genomics, genetic crosses and gene editing to demonstrate that a second vacuolar transporter plays a key role in both resistance and compensatory evolution. Longitudinal genomic analyses of the Gambian parasites revealed temporal signatures of selection on a putative amino acid transporter ( pfaat1) variant S258 L , which increased from 0% to 97% in frequency between 1984 and 2014 in parallel with the pfcrt1 K76 T variant. Parasite genetic crosses then identified a chromosome 6 quantitative trait locus containing pfaat1 that is selected by CQ treatment. Gene editing demonstrated that pfaat1 S258 L potentiates CQ resistance but at a cost of reduced fitness, while pfaat1 F313 S , a common southeast Asian polymorphism, reduces CQ resistance while restoring fitness. Our analyses reveal hidden complexity in CQ resistance evolution, suggesting that pfaat1 may underlie regional differences in the dynamics of resistance evolution, and modulate parasite resistance or fitness by manipulating the balance between both amino acid and drug transport.